Introducing the University of Applied Science in the technology transfer process - Erik E. Lehmann; Alexander Starnecker (University of Augsburg, Chair of Management and Organization, 2013)
After WWII, the German Economy increased rapidly, often described as the Deutsche Wirtschaftswunder. Within a short period, Germany reached the status of unemployment and human capital gets the critical factor and resource in shaping economic growth. While the bottle neck with blue collar workers was solved by an active immigration policy by attracting people from Italy, Turkey or Greece, the lack of white collar workers and engineers still remained. Public universities at this time weren't still unable to provide the quantity of well-educated people in particular in the natural sciences. In particular the high opportunity costs of time made public universities less attractive compared to an early carrier within the industry. In the mid of the 1960s the German government decided to adapt a well-known concept from the theory of the firm - division of labor to provide high skilled employees. A new type of university was created, the so called Universities of Applied Sciences. Public Universities are focused on basic research, while Universities of Applied Sciences (UAS) provide the economy with applied research and education. While the time spend at public universities often exceeded a couple of years before getting graded, the study program at UAS was mainly limited to 3 years (6 semesters). After the Bologna Reform, Bachelor and Master programs of UAS and public universities are treated equally. In the last decade, this division of labor between UAS and public universities was mainly focused on an additional way, the role of each type of university within the technology transfer process. While the role of public universities and their role within the technology transfer processes is intensively studied (Hülsbeck, Lehmann & Starnecker, 2012) the impact of UAS remains rather under researched. Although they are quite successful in their cooperation with the industry and are nevertheless a bone back in the university-industry relationships, there exists almost anecdotal evidence on this type of universities. This paper tries to shed some lights on this type of universities which could be a role model in particular for countries and regions where small and medium sized firms dominate the industrial landscape.
Keywords: 650